The influence of the first aid training on the knowledge of middle school students - Cierniak, Marcin; Bartczak, Maria; Balcerzyk-Barzdo, Elżbieta; Burska, Karolina; Starosta-Głowińska, Katarzyna (Polish Journal of Public Health, 2012)
Introduction. Sudden arrest of circulation (SAC) is the main reason for deaths in Europe. SAC is diagnosed in 350,000-700,000 people per year. Quick reaction and cardiopulmonary resuscitation (CPR) performed by lay observers increase the efficiency of advanced resuscitation procedures and the chances of survival in injured patients. Unfortunately, CPR is undertaken by lay observers only in 30% of patients with SAC while they are waiting for an ambulance to come. Inability to provide first aid is one of the most common reasons for not initiating CPR. By attending first aid courses people can improve their knowledge and be ready and willing to provide emergency actions.Aim. The main aim of the study was to estimate the students’ knowledge of resuscitation before and after attending such a course. Material and methods. The study included 199 pupils. The students before and after the training filled in the questionnaires on their knowledge of providing first aid in the case of SAC and body injuries. Not only general progress of the students but also their improved knowledge of various topics covered in the course (basic resuscitation or first aid procedures to the injured), were evaluated.Results. The course increased the students’ knowledge of first aid procedures by 39.5%. The majority of them property identified the place of chest compression, gave a correct ventilation/compression ratio and the right emergency telephone number.Conclusions. The course increased the students’ know-ledge. Further first aid courses and trainings are necessary to improve social awareness and knowledge how to provide first aid.